Degradasi Warna dan pH pada Air Gambut Menggunakan Metode Fotokatalisis TiO2 dengan Variasi UltraViolet - Putri, Amelia; Yuliawati, Erna; Mardwita, Mardwita (Penerbit Goodwood, 2024)
Purpose: This study aimed to evaluate the effectiveness of TiO? photocatalysis with varying UV light intensities in degrading color, reducing iron content, and improving pH in peat water, which is naturally acidic and rich in organics. Methodology: Peat water was treated using TiO? doses of 1.5 g and 2.5 g under 24 W and 32 W UV lamps for 3–6 h. The analyzed parameters included color (TCU), pH, iron (Fe), and E. coli counts. The experiments used a batch reactor with multiple UV sources to enhance the photocatalytic activity. Results: Color was completely removed (100%) under all treatment conditions. The highest Fe reduction (97.8%) occurred using 1.5 g TiO? under 24 W UV irradiation for 4 h. The highest pH increase (62.33%) was achieved using 2.5 g TiO? under 32 W UV for 6 h, raising the pH from 3.00 to 4.87. E. coli was fully eliminated in all variations. Conclusion: TiO? photocatalysis effectively removed color, iron, and bacteria from peat water. However, although the pH improved, it remained below potable water standards, indicating the need for further treatment. Limitation: The study was limited to laboratory-scale conditions and did not achieve neutral pH levels, requiring additional post-treatment and field validation for practical application. Contribution: This study highlights TiO?/UV photocatalysis as a promising method for advanced peat water treatment. This study offers insights into optimizing treatment parameters for improved water quality in future applications.